Liquid Sugar Production from Cellulosic Waste as an Alternative for IV Fluids - Lumoindong, Frans; Mamuaja, Christine F. (Pascasarjana Unsrat, 2016)
The objective of the study was to utilize the cellulose garbages in North Minahasa Regency, North Sulawesi Province and detect the liquid sugar through acidic hydrolysis. After liquid sugar production, the product could be used as raw material of health product and pharmacy, such as intravenous liquid. For food product, it can be used as food product raw material which can increase people food security and to use the cellulose wastes for liquid sugar production from cellulose wastes of corn cob, rice husk and coconut skin.This study was carried out using laboratory analysis. It applied Complete Randomized Design factorially set with 3 replications as follows: A = cellulose wastes including corn cob (A1), coconut skin (A2) and padi husk (A3), and B = hydrolysis using HCL covering 0.50% HCl (B1), 0.75% HCl (B2) and 1.0% HCl (B3). As conclusion, the cellulose wastes of corn cob, coconut skin, and rice husk were potential to producing liquid waste, in which rice husk had the highest potential. The highest glucose concentration occurred in rice husk of 1% HCL, 25%. Keywords: liquid sugar, cellulosic waste, IV fluids